Approximating inverse cumulative distribution functions to produce approximate random variables - Sheridan-Methven, O; Sheridan-Methven, O; Giles, M; Giles, M (University of Oxford, 2020)
Data generated for an article on approximating random numbers, focusing on approximating the Gaussian and non central chi-squared distributions. All source code is at https://github.com/oliversheridanmethven/approximating_inverse_cumulative_distribution_functions and https://github.com/oliversheridanmethven/approximate_random_variables and is a mix of Python, C, and a bit of C++.